Heparin induces neutrophil elastase-dependent vital and lytic NET formation. (27th December 2019) - Lelliott, Patrick M; Momota, Masatoshi; Shibahara, Takayuki; Lee, Michelle S J; Smith, Nicholas I; Ishii, Ken J; Coban, Cevayir
Abstract : Heparin induces NET formation via a novel pathway Abstract: Heparin is used extensively as an anticoagulant in a broad range of diseases and procedures; however, its biological effects are not limited to coagulation and remain incompletely understood. Heparin usage can lead to the life-threatening complication known as heparin-induced thrombocytopenia (HIT), caused by the development of antibodies against heparin/PF4 complexes. Here, we demonstrate the ability of heparin to induce neutrophil extracellular traps (NETs). NETs occurred with cell lysis and death, but live neutrophils releasing extracellular DNA strands, known as vital NETs, also occurred abundantly. Formation of NETs was time and dose dependent, and required reactive oxygen species and neutrophil elastase. Other compounds related to heparin such as low molecular weight heparin, fondaparinux and heparan sulfate either failed to induce NETs, or did so to a much lesser extent. Our findings suggest the ability of heparin to directly induce NET formation should be considered in the context of heparin treatment and HIT pathogenesis.